Ex vivo comparison of standing and recumbent repair of incomplete parasagittal fractures of the first phalanx in horses. Issue 4 (12th March 2021) - Labens, Raphael; Jermyn, Kieri
Abstract: Objective: To assess suspensory ligament extensor branch location and fracture gap reduction with simulation of standing and recumbent cortical bone screw repair of experimental incomplete parasagittal proximal phalanx (P1) fractures. Study design: Controlled laboratory study. Sample population: Twenty equine cadaver forelimbs. Methods: Simulated fractures were repaired twice in random order. A proximal cortical bone screw was placed in lag fashion with the limb unloaded (simulated recumbent repair) and loaded to 38% of body weight (range, 375–568 kg; simulated standing repair). Changes in fracture gap width were assessed on computed tomography (CT) images and with intraplanar force‐sensitive resistors measuring voltage ratios (V△ ) between loaded recumbent (R‐1) and standing repair simulations (R‐2). Extensor branch borders were determined relative to implant position and sagittal P1 width on transverse CT images. P  ≤ .05 was considered significant. Results: Standing repair simulation‐associated fracture gaps were not wider than in R‐1 while controlling for confounding factors (loading weight, implant position, or animal age; P  > .7, repeated‐measures analysis of variance). Voltage ratio data associated with R‐2 were not smaller than with R‐1 (mean difference, 0.002 ± 0.052; one‐sided Wilcoxon signed‐rank test, P = .27). More of P1 width was approachable palmar to extensor branches when limbs were loaded (0.804 ± 0.314 cm) vs unloaded (0.651 ± 0.31 cm; paired Student's t test, P  < .001). Conclusion: Simulated standing repair was not associated with inferior fracture reduction compared with loaded simulations of recumbent repairs. Limb loading affected extensor branch location relevant to implant positioning. Clinical significance: Unloading during standing repair of incomplete parasagittal proximal P1 fractures may not be required to optimize fracture reduction.